Body Mass Index, Hamstring and Low Back Flexibility in Young Adults - Neha Mukkamala; Ashwini Gite; Lata Parmar; Purvi Patel (Research Aspects in Biological Science Vol. 5, 2022)
Body Mass Index is an important index for disease prediction. Flexibility is an important physical parameter related to an athlete’s performance and muscle injury. Poor flexibility of the hamstrings muscle is associated with muscle strains, patellofemoral pain and low back pain. So it is important to study the relationship between BMI, Hamstring and low back flexibility. The active knee extension test (AKET) and the straight leg raise test (SLR) are the most commonly used tests for assessing hamstring tightness. They also have excellent inter-rater and intra-rater reliability. A study found average hamstring tightness using Active knee extension test for right and left side to be 36.6±11.550 & 31.4±12.480 respectively. The flexibility of the hamstring and low back using Sit and reach test was 21.9±7.6 cm which was poor. However, there was no statistically significant correlation between BMI and flexibility. Almost 90% of the participants were in the poor-fair category of flexibility, which was similar across all BMI categories. 61% of the young adults in the study were found inactive, which was one of the reasons for decreased flexibility.